Pengaruh Disiplin Kerja dan Motivasi Terhadap Kinerja Pegawai Pengadilan Negeri Karawang Kelas 1b - Widya Sri Hartati; Suroso; Syifa Pramudita Faddila (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research is to examine the influence of work discipline and motivation on performance. This research uses quantitative methodology through a verification approach, a sample of 75 people from Class 1B Karawang District Court employees. Correlation test results with a sig value of 0.001 < 0.05. So it can be concluded that there is a correlation between the independent variable work discipline and the dependent variable performance. Correlation test results with a sig value of 0.001 < 0.05. It can be concluded that motivation has a positive and significant effect on performance. The calculated F calculation results are 93.290 > Ftable 3.12, and the sig value is 0.001 < 0.05, so Ho is rejected. Based on these two test results, there is a simultaneous influence between work discipline and motivation variables on performance of 72.2%, the remaining 27.8% is influenced by other variables not measured in this research